2004
DOI: 10.1099/jmm.0.05460-0
|View full text |Cite
|
Sign up to set email alerts
|

Autolysin-targeted LightCycler assay including internal process control for detection of Streptococcus pneumoniae DNA in clinical samples

Abstract: The development and clinical evaluation of a LightCycler PCR assay, including an internal process control (IPC), to detect the Streptococcus pneumoniae autolysin gene in clinical samples is reported. The assay was developed to provide a second target for use in conjunction with existing pneumolysin PCR assays to increase the reliability of non-culture PCR diagnosis of pneumococcal infection. Primers amplify a 173 bp fragment of the autolysin gene (lytA), which is detected by fluorescence-labelled hybridization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 21 publications
4
67
1
Order By: Relevance
“…The methods for the two pneumococcal PCRs, the pneumolysin-targeted TaqMan assay and autolysin-targeted LightCycler assay, have been described previously (14,15). All EDTA blood samples (200-l volume) were extracted using the MagNA Pure Total NA isolation system (Roche Diagnostics) by following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods for the two pneumococcal PCRs, the pneumolysin-targeted TaqMan assay and autolysin-targeted LightCycler assay, have been described previously (14,15). All EDTA blood samples (200-l volume) were extracted using the MagNA Pure Total NA isolation system (Roche Diagnostics) by following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In general, when performed on sputum samples they have good sensitivity but poor specificity (12,17). In order to overcome the latter problem, PCR assays have been evaluated on blood samples (5,8,14,15), giving excellent specificity but relatively poor sensitivity. Consequently, in an attempt to improve sensitivity but maintain good specificity, we have devised a dual-PCR testing protocol that tests for two pneumococcal targets (lytA and ply) in duplicate samples.…”
mentioning
confidence: 99%
“…al. [17] have published an accurate meta-analysis and found that the studies were highly heterogeneously including different type of PCR methods [18,19], different target genes [20], most used stored frozen [21] and different samples (i.e. whole blood or plasma) [22], as well as different patients' characteristics and different clinical syndromes [23,24].…”
Section: Reproducibility and Specificity Of Real-time Pcrmentioning
confidence: 99%
“…New sensitive diagnostic methods would be valuable not only for determining the etiology of individual infections but also for monitoring the epidemiology of pneumococcal disease within the general population and vaccine recipients in particular. Application of PCR assays for the diagnosis of invasive pneumococcal disease has proven to be of limited success because they are insufficiently sensitive when applied to blood or urine and are not infection specific when applied to respiratory samples (12,19). A number of publications have described antigen detection assays (7,9).…”
mentioning
confidence: 99%